Resource‐Rational Virtual Bargaining for Moral Judgment: Toward a Probabilistic Cognitive Model - Trujillo, Diego; Zhang, Mindy; Zhi‐Xuan, Tan; Tenenbaum, Joshua B.; Levine, Sydney (Topics in cognitive science, 2025)
Recent theoretical work has argued that moral psychology can be understood through the lens of “resource rational contractualism.” The view posits that the best way of making a decision that affects other people is to get everyone together to negotiate under idealized conditions. The outcome of that negotiation is an arrangement (or “contract”) that would lead to mutual benefit. However, this ideal is seldom (if ever) practical given the resource demands (time, information, computational processing power) that are required. Instead, the theory proposes that moral psychology is organized around a series of resource‐rational approximations of the contractualist ideal, efficiently trading off between more resource‐intensive, accurate mechanisms and less. This paper presents empirical evidence and a cognitive model that test a central claim of this view: when the stakes of the situation are high, then more resource‐intensive processes are engaged over more approximate ones. We present subjects with a case that can be judged using virtual bargaining—a resource‐intensive process that involves simulating what two people would agree to—or by simply following a standard rule. We find that about a third of our participants use the resource‐rational approach, flexibly switching to virtual bargaining in high‐stakes situations, but deploying the simple rule when stakes are low. A third of the participants are best modeled as consistently using the strict rule‐based approach and the remaining third as consistently using virtual bargaining. A model positing the reverse resource‐rational hypothesis (that participants use more resource‐intensive mechanisms in lower stakes situations) fails to capture the data. Contractualism posits that people make moral judgments by considering what contracts would be negotiated under idealized circumstances. This paper tests a central hypothesis of “resource rational contractualism” — that people use more accurate, resource‐intensive processes (such as virtual bargaining) to predict negotiated agreements when stakes are high.